CAPITALISM AND THE COMMODIFICATION OF RAMADAN IN INDONESIAN CONTEXT - Mohammad Muafi Himam; Hammis Syafaq (UIN Raden Mas Said Surakarta, 2025)
This article critically examines the commodification of Ramadan fasting rituals through a Marxist perspective. Situated within the discourse of Marxist social critique, it investigates how capitalism transforms religious practices into commercialized spectacles and ideological instruments. Drawing upon a conceptual and theoretical approach through critical literature review, this study synthesizes classical Marxist theories from Marx and Engels, as well as neo-Marxist frameworks including Gramsci’s concept of hegemony, the Frankfurt School’s critique of commodification, and Althusser’s theory of ideological state apparatuses. The analysis engages with empirical illustrations such as advertising strategies, shifting consumption patterns during Ramadan, and state-sponsored religious campaigns. This study is conceptual and does not rely on original field data, but instead critically analyzes existing literature and socio-cultural phenomena. The findings reveal the dual function of Ramadan within capitalist society: as a cultural critique of consumerism grounded in simplicity, empathy, and social solidarity, and simultaneously as a tool co-opted to reinforce consumerism, class stratification, and hegemonic ideology. By highlighting how Ramadan rituals subvert and support capitalist structures, this paper contributes to scholarly discourse on the intersection of religion, ideology, and political economy in contemporary Muslim societies.